2017
DOI: 10.18203/2349-2902.isj20164427
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing laparoscopic and open ventral hernia repair

Abstract: INTRODUCTIONA ventral hernia is defined as a fascial defect located in the abdominal wall. Primary ventral hernias have been classified as umbilical, epigastric, Spighelian and lumber hernias, and secondary ventral hernias are incisional hernias that have developed from previous postoperative scars. 1 Ventral hernia repair is a common surgical procedure. Mostly, ventral hernias are small umbilical and epigastric hernias, but almost 30% of these procedures are incisional hernia repair is and around half of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Laparoscopic repair of ventral hernia is showing promising results and is being widely practiced now-a-days. 13,14 Postoperative pain and hospital stay is lesser and there is faster resumption of routine activities after laparoscopic procedure. In spite of all the advantages, laparoscopic repair may have several disadvantages like need for general anaesthesia, higher operative cost, incompatibility for patient's status like cardiorespiratory insufficiency, abnormalities of haemostasis and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic repair of ventral hernia is showing promising results and is being widely practiced now-a-days. 13,14 Postoperative pain and hospital stay is lesser and there is faster resumption of routine activities after laparoscopic procedure. In spite of all the advantages, laparoscopic repair may have several disadvantages like need for general anaesthesia, higher operative cost, incompatibility for patient's status like cardiorespiratory insufficiency, abnormalities of haemostasis and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding was observed in a study conducted by Ruby et al in a prospective study comparing laparoscopic and open ventral hernia repair found majority (50%) of the patients were in the 4th to 6th decade. 15 Predominance of older age group might be attributed to weakening of abdominal muscles, delayed healing and additional age related co morbidities.…”
Section: Age Distributionmentioning
confidence: 99%
“…A ventral hernia occurs due to a weakness in the musculofascial layer of the anterior abdominal wall [ 1 ]. Ventral hernia includes paraumbilical, epigastric, Spigelian, and incisional hernias [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%